PENGARUH QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - Sugiarta, I Gusti Oka; Adnyani, I Gusti Ayu Dewi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Employee performance is an important thing to advance a company, good performance is needed so that company goals can be achieved. Several factors that affect an employee's performance include quality of work life and organizational commitment. This study aims to analyze the effect of quality of work life on employee performance with organizational commitment as a mediating variable. Samples were taken as many as 58 employees and using saturated samples. Data collection in this study was carried out by interview and questionnaire methods. The data analysis technique used in this research is Path Analysis and Sobel Test. Based on the results of the analysis, it was found that the quality of work life has a positive and significant effect on employee performance, the quality of work life has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on employee performance, organizational commitment is a mediating variable from the influence of quality of work life. on employee performance.